The impact of an integrative 3-d virtual learning environment in diverse ninth grade earth and space science classes - Fenwick, Emily L. (Kansas State University, 2010)
Problem-based learning in the sciences has been demonstrated to be a successful educational approach to engage students and increase content knowledge. However, the power of collaborative learning to engage students, increase content knowledge and develop problem-solving skills in the sciences has not yet been fully researched. Collaborative learning has an enormous potential not only to foster student learning, but also to increase interest in the sciences and promote cutting-edge education strategies worldwide. Collaborative learning tactics in this study take place within the virtual learning environment entitled “GeoWorlds.” GeoWorlds is an online educational gaming program within the Second Life 3-D Teen Grid. The curriculum was developed as a collaborative, investigative and engaging program to promote learning of Earth science content. The program allows students to be submersed-in and explore different geologic time periods; enabling them to observe species and geological structures while interacting with one another to complete tasks. This study investigates the educational impact, emotional response and overall feedback of the GeoWorlds virtual learning environment on Midwest ninth graders.
Keywords: Education; Geoscience; Virtual Learning Environment; Second Life; Education, Sciences (0714); Geology (0372)